Oral immunization of mice with Omp31-loaded N-trimethyl chitosan nanoparticles induces high protection against Brucella melitensis infection - Abkar M (Dove Medical Press, 2017)
Morteza Abkar,1 Mahdi Fasihi-Ramandi,2 Hamid Kooshki,3 Abbas Sahebghadam Lotfi4 1Nanomedicine and Nanobiology Research Center, Shiraz University of Medical Sciences, Shiraz, 2Molecular Biology Research Center, 3Nanobiotechnology Research Center, Baqiyatallah University of Medical Sciences, 4Department of Clinical Biochemistry, Faculty of Medicine, Tarbiat Modares University, Tehran, Iran Abstract: Brucellosis is a group of closely associated zoonotic bacterial illnesses caused by members of the genus Brucella. B. melitensis Omp31 is a promising candidate for a subunit vaccine against brucellosis. This study surveyed the immunogenicity of Omp31 alone and with incomplete Freund’s adjuvant (Omp31-IFA) and N-trimethyl chitosan (TMC/Omp31) nanoparticles (NPs), as well as the effect of Omp31 immunization route on immunological responses and protection. After expression and purification, the recombinant Omp31 (rOmp31) was loaded onto TMC NPs by ionic gelation. The particle size, loading efficiency and in vitro release of the NPs were examined. Omp31-IFA was administered intraperitoneally, while TMC/Omp31 NPs were administered orally and intraperitoneally. According to the antibody subclasses and cytokine profile, intraperitoneal immunization by Omp31-IFA and TMC/Omp31 NPs induced T helper 1 (Th1) and Th1–Th2 immune responses, respectively. On the other hand, oral immunization with TMC/Omp31 NPs elicited a mixed Th1–Th17 immune response. Data obtained from the cell proliferation assay showed that vaccination with Omp31 stimulated a vigorous antigen-specific cell proliferative response, which could be further increased after oral immunization with TMC/Omp31 NPs. Vaccinated groups of mice when challenged with B. melitensis 16M were found to be significantly protected in the orally administered group in comparison with the intraperitoneally immunized mice. Results of this study indicated that the reason for high protection after oral vaccination can be via elicited Th17 response. Keywords: brucellosis, Th17, trimethyl chitosan, vaccine, nanoparticle